Adaptive Fuzzy Logic Control of Wind Turbine Emulator - Bouzid Mohamed Amine; Zine Souhila; Allaoui Tayeb; Massoum Ahmed (Institute of Advanced Engineering and Science, 2014)
In this paper, a Wind Turbine Emulator (WTE) based on a separately excited direct current (DC) motor is studied. The wind turbine was emulated by controlling the torque of the DC motor. The WTE is used as a prime mover for Permanent Magnet Synchronous Machine (PMSM). In order to extract maximum power from the wind, PI and Fuzzy controllers were tested. Simulation results are given to show performance of proposed fuzzy control system in maximum power points tracking in a wind energy conversion system under various wind conditions. The strategy control was implemented in simulation using MATLAB/Simulink.DOI: http://dx.doi.org/10.11591/ijpeds.v4i2.5809